Micro- and macro-habitat selection of Atlantic salmon, Salmo salar, post-smolts in relation to marine environmental cues. (20th April 2022) - Jensen, J L A; Strøm, J F; Nikolopoulos, A; Primicerio, R; Skarðhamar, J; Atencio, B J; Strand, J E T; Bjørn, P A; Bøhn, T
Abstract: Atlantic salmon is an economically and culturally important species. The species encounters several natural and man-made threats during its migration between fresh water and the ocean, which in combination may explain its ongoing decline. With the aim to better understand whether post-smolt behaviour is influenced by physical oceanographic conditions, the migratory behaviour of 173 post-smolts in a high-latitude Norwegian fjord was investigated, combining acoustic telemetry with site- and time-specific environmental variables from an oceanographic model. Most post-smolts (94%) performed a unidirectional migration out the fjord. Progression rates were relatively high (0.42–2.41 km h −1 ; 0.84–3.78 BL s −1 ) and increased with distance from the river. While post-smolts had an affinity for lower salinities in the inner fjord, statistical models failed to detect any significant relationship between the small-scale (within arrays) migratory behaviour and salinity, temperature, or coastal surface currents within the fjord. In the outer part, the post-smolts predominantly exited the fjord system through the strait with the highest surface salinities and lowest temperatures, independently of the current direction. Our findings indicate that the macro- habitat selection of the Atlantic salmon post-smolts was influenced by environmental factors: the post-smolts directed their migration towards "ocean cues." However, this was not confirmed on the micro -habitat level.